2003
DOI: 10.1001/archotol.129.9.994
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Irregular Voices After Total and Laser Surgical Partial Laryngectomy

Abstract: The Göttingen hoarseness diagram is suitable for a qualitative assessment even of irregular voices. Voice prosthesis offers a voice quality that at best approaches that of patients with partial laryngectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
1
6

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 16 publications
1
33
1
6
Order By: Relevance
“…Vocal samples of the partial laryngectomy group were located, in its great majority, in the upper right quadrant, corroborating a study in which post-partial laryngectomy voices obeyed the same location 16 . The perceptual analysis when associated to the acoustic analysis revealed that, of the eight voices (57,2%) of subjects submitted to partial laryngectomy that were classified as degree 3, six (42,8%) were located in the upper right quadrant confirming the findings of a study that affirms that the worse the dysphonia the higher the chance of the vocal sample be located in the upper right…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Vocal samples of the partial laryngectomy group were located, in its great majority, in the upper right quadrant, corroborating a study in which post-partial laryngectomy voices obeyed the same location 16 . The perceptual analysis when associated to the acoustic analysis revealed that, of the eight voices (57,2%) of subjects submitted to partial laryngectomy that were classified as degree 3, six (42,8%) were located in the upper right quadrant confirming the findings of a study that affirms that the worse the dysphonia the higher the chance of the vocal sample be located in the upper right…”
Section: Resultssupporting
confidence: 82%
“…The diagram is based in four acoustic measures: three of them related to irregularity of the sound signal -jitter, shimmer and their correlation; the fourth one is related to the noise component, named glottal to noise excitation ratio -GNE [13][14][15] . The differential of this diagram is that it is able to assess very deviant voices, besides showing differences between dysphonic groups with different phonatory mechanisms and it allows monitoring of vocal quality 10,[13][14][15][16][17] . The GNE is the acoustic measure that calculates the noise produced by the oscillation of vocal chords.…”
Section: Methodsmentioning
confidence: 99%
“…Studies on the utilization of the PDD in voice evaluation 10,12,17 have shown that the diagram is effective in analyzing the regularity of the sound signal and the additive noise component, thus providing information on the characteristics of the voice production of healthy and dysphonic individuals.…”
mentioning
confidence: 99%
“…This may be interpreted to mean that the patients were less affected emotionally when using their voices, although they were physically and functionally strained. In the study by Olthoff et al (26) on total laryngectomy patients with voice prosthesis and patients who underwent partial laryngectomy with transoral laser surgery, both patient groups graded their voices as "well" in the questionnaire performed for evaluation purposes. Therefore, it can be sufficient to have a posttreatment communication language for most patients with larynx cancer.…”
Section: Discussionmentioning
confidence: 99%